C++ solutions for mathematical problems - Ghosh, Arun, 1933- (New Age International (P) Ltd., Publishers, 2005)
The presentation of this book is on the comprehensible application of techniques for the approximation of the mathematical problems that are frequently observed in physical sciences, engineering technology and mathematical physics. The acceptance of the technique for the solution has been justified from mathematical point of view. The Software required for the approximate solution of the problems applying the appropriate Methods, numerically developed is the set of programs written in C++ (Turbo).